EVALUATION OF SOLID MEDICAL WASTE MANAGEMENT SYSTEM OF PUSKESMAS IN CIANJUR DISTRICT - Edo Muhammad; Tri Joko; Nurjazuli Nurjazuli (Journal of Public Health for Tropical and Coastal Region, 2019)
Some of the waste produced by community health centers is hazardous waste and can pose a number of health and environmental risks if management is not in accordance with the requirements. This study aims to evaluate the conditions for managing solid medical waste in the Cianjur Regency community health center. This type of research is a qualitative descriptive study. The results of the study show that the public health center with the HR condition is quite 90% and less 10%. Public health center with budget conditions in good category 73.3%, and quite 26.7%. Community health center with a condition of facilities and infrastructure of less than 50% category, and quite 50%. Community health centers with SOP conditions in the category of both 90%, and less than 10%. Public health center with conditions for sorting and storing good categories of 46.7%, and enough of 53.3%. all community health centers have sufficient conditions for collecting medical waste. Community health center with conditions for transporting medical categories of waste both 60%, enough 26.7%, and less 13.3%. Community health center with temporary storage conditions medical waste is quite 83.3%, and less 16.7%. a public health center whose medical waste management officers had experienced an accident of 13.3%, whose officers had never had an accident of 86.7%. The conclusion of this study is that most public health center medical waste management is in accordance with the requirements, which are not yet appropriate are aspects of HR, facilities and infrastructure, sorting, use of PPE and Temporary Storage Places.